Nutritional composition, antioxidant activity and isolation of scopoletin from Senecio nutans: support of ancestral and new uses. Issue 6 (19th March 2018) - Parra, Claudio; Soto, Emilio; León, Gloria; Salas, Cristian O.; Heinrich, Michael; Echiburú-Chau, Carlos
Abstract: Continuing with our study characterising Senecio nutans Sch. Bip., we have isolated and identified a simple coumarin, scopoletin, that could be relevant for the biological properties of the species related with the ancestral medical uses. This is the first report of scopoletin from S. nutans . In addition, the extract was analysed for its antioxidant activity using the ABTS and FRAP method as well as providing the first nutritional analyses of this plant from northern Chile highlands. Abstract :